Neural Oscillation During Mental Imagery in Sport: An Olympic Sailor Case Study - Budnik-Przybylska, Dagmara; Kastrau, Adrian; Jasik, Patryk; Kaźmierczak, Maria; Doliński, Łukasz; Syty, Paweł; Łabuda, Marta; Przybylski, Jacek; di Fronso, Selenia; Bertollo, Maurizio (Frontiers in Human Neuroscience, 2021)
The purpose of the current study was to examine the cortical correlates of imagery depending on instructional modality (guided vs self-produced) using various sport related scripts. According to the expert-performance approach, we took an idiosyncratic perspective analyzing the mental imagery of an experienced two-time Olympic athlete to verify whether different instructional modalities of imagery (i.e., guided vs self-produced) and different scripts (e.g. training or competition environment) could differently involve brain activity. The subject listened to each previously recorded script taken from two existing questionnaires concerning imagery ability in sport and then was asked to imagine the scene for a minute. During the task, brain waves were monitored using EEG (32-channel g. Nautilus). Our findings indicate that guided imagery might induce higher high alpha and SMR (usually associated with selective attention), whereas self-produced imagery might facilitate higher low alpha (associated with global resting state and relaxation). Results are discussed in light of the neural efficiency hypothesis as a marker of optimal performance and transient hypofrontality as a marker of flow state. Practical mental training recommendations are presented.